SOUND CHANGE IN JAPANESE WAKAMONO KOTOBA: MORPHOPHONEMIC AND SEMANTIC STUDY - Julia Angelina; Utari Novella (LLDIKTI Wilayah X, 2022)
Wakamono kotoba is a language that always change. In wakamono kotoba, sound change phenomenon could be found and affected the word class and word meaning. The purpose of this research is to understand what kind of sound change that occurred to wakamono kotoba, word formation and meaning change happened. The research used qualitative research methodology from library study with descriptive analysis method. Theories used were morphophonemic theory stated by Koizumi (1993) and Suzuki (1975), word formation theory stated by Sakuma (2008), denotative and connotative meaning stated by Sakuma (2008) and meaning expansion-reduction by Saito (2013). The data was taken from a ranking article of wakamono kotoba in Jikitourai website. From this research, it can be concluded that in wakamono kotoba, there are 9 patterns of sound change in which 5 are new patterns, 7 types of word formation with one new formation, and not all wakamono kotoba undergo meaning change.